Review of the Accuracy of Diagnosis Codefication of Obstetric Cases Category Abortion at RSUD X in Cirebon Regency in 2024 - Safitri, Cahya Wulan; Aryani, Bhakti; Haryanto, Yanto; Rahmawati, Fitria Dewi (LPPM Universitas Dhyana Pura, 2025)
Abortion or miscarriage is the death of the fetus when the gestational age is <20 weeks or the fetal weight is <500 grams. Post miscarriage / abortion care is an approach to treating mothers after a miscarriage, either spontaneously or through induction. This is in line with one of the Sustainable Development Goals (SDGs), which is to reduce the maternal mortality ratio (MMR) to 70 per 100,000 live births in Indonesia by 2030. Researchers used a quantitative descriptive method with a total sampling technique of 75 medical record documents of inpatients with abortion cases in 2024. The purpose of this study was to determine the percentage of accuracy of the diagnosis code of obstetric cases in the abortion category at RSUD X, Cirebon Regency. This study used descriptive quantitative with total sampling technique. The samples in this study were 75 medical record documents of inpatient obstetric cases of abortion category in 2024 at RSUD X, Cirebon Regency. Data were collected and then analyzed using univariate analysis or descriptive analysis to describe or describe the data that had been collected. The results showed that 54 documents (72%) with appropriate codes and 21 documents (28% with inappropriate codes). Of the 21 documents with inappropriate codes, 15 documents (71.5%) had incorrect diagnosis writing by DPJP.